Expectativas gerais de Angola para os 50 anos de independência em 2025: Desafios e oportunidades num contexto internacional em mutação - Almeida, E. C. (Figuras & Negócios, 2024)
Analysis of the expectations that Angola may have in the year of the celebration of its 50th independence anniversary, in light of the current international political and economic events, which are volatile due to the new political conditions in the international arena, particularly in the USA, with the upcoming administration led by Trump, whose approach to Africa in general, and Angola in particular, remains uncertain.